An enhanced russell measure of super-efficiency for ranking efficient units in data envelopment analysis - Ashrafi, Ali; Jaafar, Azmi; Lee, Lai Soon; Abu Bakar, Mohd Rizam (Science Publications, 2011)
Problem statement: Conventional Data Envelopment Analysis (DEA) helps decision makers to discriminate between efficient and inefficient Decision Making Units (DMUs). However, DEA does not provide more information about the efficient DMUs. Super-efficiency DEA model can be used in ranking the performance of efficient DMUs. Because of the possible infeasibility of radial super-efficiency DEA model, the ranking has been limited to the model under the assumption of Constant Returns to Scale (CRS). Approach: This study proposes a super-efficiency model based on the Enhanced Russell Measure (ERM) of efficiency. This is a non-radial measure and appropriate for ranking the efficient DMUs when inputs and outputs may change non-proportionally. Results: Theoretical results show that the new super-efficiency model is always feasible under the assumption of non-CRS. Also, numerical examples from the literature are provided to test the new super-efficiency approach. Conclusion: This study provides a non-radial measure of super-efficiency based on the ERM model to discriminate among the efficient DMUs resulting different efficiency scores greater than one. Unlike the traditional radial super-efficiency models, the proposed method is always feasible.